First cross-border outbreak of foodborne botulism in the European Union associated with the consumption of commercial dried roach (Rutilus rutilus) - Hendrickx, David; Varela Martínez, Carmen; Contzen, Matthias; Wagner-Wiening, Christiane; Janke, Karl-Heinz; Hernando Jiménez, Pablo; Massing, Susanne; Pichler, Jeanette; Tichaczek-Dischinger, Petra; Burckhardt, Florian; Stark, Klaus; Katz, Katharina; et al. (Frontiers in Public Health, 2023)
Botulism outbreaks due to commercial products are extremely rare in the European Union. Here we report on the first international outbreak of foodborne botulism caused by commercial salt-cured, dried roach (Rutilus rutilus). Between November and December 2016, an outbreak of six foodborne botulism type E cases from five unrelated households was documented in Germany and Spain. The outbreak involved persons of Russian and Kazakh backgrounds, all consumed unheated salt-cured, dried roach – a snack particularly favored in Easter-European countries. The implicated food batches had been distributed by an international wholesaler and were recalled from Europe-wide outlets of a supermarket chain and other independent retailers. Of interest, and very unlike to other foodborne disease outbreaks which usually involves a single strain or virus variant, different Clostridium botulinum strains and toxin variants could be identified even from single patient’s sample. Foodborne botulism is a rare but potentially life-threatening disease and almost exclusively involves home-made or artisan products and thus, outbreaks are limited to individual or few cases. As a consequence, international outbreaks are the absolute exception and this is the first one within the European Union. Additional cases were likely prevented by a broad product recall, underscoring the importance of timely public health action. Challenges and difficulties on the diagnostic and epidemiological level encountered in the outbreak are highlighted.